Different subpopulations of macrophages, neutrophils, mast cells, and fibroblasts are involved in the control of tumor angiogenesis - Ribatti, Domenico (Frontiers in Medicine, 2024)
The tumor microenvironment comprises diverse cell types, including T and B lymphocytes, macrophages, dendritic cells, natural killer cells, myeloid-derived suppressor cells, neutrophils, eosinophils, mast cells, and fibroblasts. Cells in the tumor microenvironment can be either tumorsuppressive or tumor-supporting cells. In this review article, we analyze the double role played by tumor macrophages, tumor neutrophils, tumor mast cells, and tumor fibroblasts, in promoting angiogenesis during tumor progression. Different strategies to target the tumor microenvironment have been developed in this context, including the depletion of tumor-supporting cells, or their "re-education" as tumor-suppressor cells.